LITERASI TEKNOLOGI DAN LITERASI DIGITAL UNTUK MENUMBUHKAN KETERAMPILAN BERWIRAUSAHA BAGI KELOMPOK PEMUDA DI KOTA MADIUN - Eni Winarsih; Yunita Furinawati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Rapid technological and digital advances must be balanced with knowledge and skills that bring benefits in life. Utilization of internet and smartphone networks among teenagers should be more directed to positive things, one of which is to use it to foster entrepreneurial skills with online businesses. This Community Partnership Program works with “Youth House Madiun”, an organization of youth and students in Madiun City. The aim of this digital literacy and technology literacy training is to give skills to the youth to use the internet network for entrepreneurship with online businesses. Online business is now more in demand by the public. The method used was online training and mentoring. The training is carried out in two phases with the material covering:Keywords : digital literacy, online business, youth